Strategies and Impacts of The Sukabumi Reading Enthusiast Program on Community Literacy - Kobasah, R. Histato Dayanto; Nurhayati, Sri (Jurnal Simki Pedagogia, 2024)
This study aimed to explore the strategies and impacts of the Sukabumi Reading Enthusiast Program on fostering community literacy and reading habits within the community. Employing a descriptive method, data were collected through observation, study of the documents and interviews with 25 participants to provide comprehensive insights into the program's effectiveness. The data were analyzed using thematic analysis and triangulation. The findings reveal that the program's structured and habitual activities, such as the weekly Readhaton sessions and daily reading practices before school lessons, significantly enhance reading engagement among participants. These activities, embedded into the school curriculum and supported by community involvement, have led to a notable increase in reading interest and proficiency. The selection of diverse and age-appropriate reading materials, tailored to the needs and preferences of the community, further supports the program's success. Moreover, the program's impact extends beyond immediate participants, fostering a culture of reading that involves families and public spaces. The study highlights the program's success in increasing the number of books read, the time spent reading, and overall participation in community reading activities. These outcomes demonstrate the program's efficacy in promoting literacy, enhancing creative thinking, and developing sustainable reading habits among community members.